2021
DOI: 10.3390/ijms222313058
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Trichoderma harzianum and Its Metabolites to Protect Wheat Seedlings against Fusarium culmorum and 2,4-D

Abstract: Wheat is a critically important crop. The application of fungi, such as Trichoderma harzianum, to protect and improve crop yields could become an alternative solution to synthetic chemicals. However, the interaction between the fungus and wheat in the presence of stress factors at the molecular level has not been fully elucidated. In the present work, we exposed germinating seeds of wheat (Triticum aestivum) to the plant pathogen Fusarium culmorum and the popular herbicide 2,4-dichlorophenoxyacetic acid (2,4-D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 50 publications
1
6
0
Order By: Relevance
“…This inhibition was probably caused by a reduction in the size of pathogenic mycelium and/or the interference of Fusarium and Trichoderma metabolic pathways. Similar studies were carried out [ 31 , 36 , 40 ] and very similar results were obtained by Tian et al [ 40 ], who observed in bi-cultures of F . graminearum and various Trichoderma strains that ZEN biosynthesis was inhibited by 9% to 97%, α-ZOL by 31% to 87% and β-ZOL by 34% to 89%.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This inhibition was probably caused by a reduction in the size of pathogenic mycelium and/or the interference of Fusarium and Trichoderma metabolic pathways. Similar studies were carried out [ 31 , 36 , 40 ] and very similar results were obtained by Tian et al [ 40 ], who observed in bi-cultures of F . graminearum and various Trichoderma strains that ZEN biosynthesis was inhibited by 9% to 97%, α-ZOL by 31% to 87% and β-ZOL by 34% to 89%.…”
Section: Discussionsupporting
confidence: 88%
“…In our experiment, the biosynthesis of mycotoxins tested was inhibited by 12% to 99%, 23% to 100%, and 13% to 100%, respectively. Mironenka et al [ 36 ] also observed that the presence of T . harzianum in co-culture with F .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Other SM can regulate virulence genes from the pathogen, such as Epl-1 from T. harzianum , which represses virulence genes in B. cinerea , and induces SA- mediated defense pathway and priming in tomato plants, conferring resistance to the pathogen [ 119 ]. SM from culture filtrates of T. harzianum and the fungus diminished the adverse effects that Fusarium culmorum causes in wheat plants, such as reduced germination or lower plant growth, and modified antioxidant enzymatic activity, overall conferring protection against the pathogen [ 122 ].…”
Section: Biocontrol Potential Of Registered Trichoderma ...mentioning
confidence: 99%
“…The present work may be the first study on the influence of low-density polyethylene (LDPE) microparticles on the soil-borne fungus Trichoderma harzianum KKP 534. In our previous study, the fungus was found to promote plant growth and limit the development of pathogenic fungi, such as Fusarium , Pythium , and others [ 35 ]. The present study assessed the effect of MPs on the growth of the fungus and the degradation of metolachlor (MET), which is a chloroacetanilide herbicide commonly used in cereal crops.…”
Section: Introductionmentioning
confidence: 99%